IMPLEMENTASI TAX PLANNING SEBAGAI UPAYA EFISIENSI PAJAK PENGHASILAN (PPh) BADAN PADA PT YATAHARAKU TIJARA ABADI - Fatahul Rahman; Chottam Chottam; Nur Halimah (Politeknik Negeri Samarinda, 2019)
This research aims to know the implementation of tax planning and calculate how efficient the income tax by using tax planning. The object used in this research is one of the coal companies that exist, namely PT Yataharaku Tijara Abadi using a descriptive quantitative method. The analysis tool used is UU No. 36 year 2008 on income tax and formula that use as comparator. The research results of the implementation of tax planning on PT Yataharaku Tijara Abadi that the company can streamline its income tax burden by holding the cost of Human development, adding food costs, entertainment costs, and salary costs for employees. The purpose of adding this cost can reduce the value of profit so that the tax burden becomes smaller. Keywords: Tax Planning, taxation efficiency, income tax.